Design and implementation of OpenStack cloud platform for different storage modes - Weibin FENG; Yunyong ZHANG; Zhijun WANG (Dianxin kexue)
With the development of cloud computing，it is more convenient to implement cloud platform by using open source software，cloud platforms usually use local hard disk or shared storage to store virtual machine file. In view of the advantages and disadvantages of these two kinds of storage modes，a method supporting two kinds of storage modes in cloud platform building based on OpenStack was presented. Users specified different parameters to create virtual machine in a corresponding storage mode，so as to meet the needs of different storage business. The method solved the support of cloud platform for different storage modes，promoted the existing network system to migrate to OpenStack cloud platform and played an important role in cloud service platform.